Landmark-based morphometric analysis in selected species of serranid fishes (Perciformes: Teleostei) - Cavalcanti, Mauro José; Monteiro, Leandro Rabello [UNESP]; Lopes, Paulo Roberto Duarte (My University, 1999)
Mauro José Cavalcanti, Leandro Rabello Monteiro and Paulo Roberto Duarte Lopes (1999) Landmark-based morphometric analysis in selected species of serranid fishes (Perciformes: Teleostei). Zoological Studies 38(3): 287-294. Morphological differences among 6 species of marine fishes belonging to 2 subfamilies of the family Serranidae (Serraninae: Dules auriga, Diplectrum formosum, and D. radiale; Epinephelinae: Epinephelus marginatus, Mycteroperca acutirostris, and M. bonaci) were studied by the geometric morphometric method of thin-plate splines and multivariate analysis of partial-warp scores. The decomposition of shape variation into uniform and nonaffine components of shape change indicate that major differences among species are related to both components of shape variation. Significant differences were found among species with respect to the uniform components, but there is no clear separation of taxonomic groups related to these components, and species are instead separated on the basis of body height and caudal peduncle length. Non-uniform changes in body shape, in turn, clearly differentiate the species of Serraninae and Epinephelinae. These shape changes are probably related to differences in habitat and feeding habits among the species.
Keywords: Geometric morphometrics; Multivariate analysis; Partial-warp scores; Serranidae; Truss networks